SUPPLY CHAIN AND VALUE ADDED OF JAVA PREANGER MANGLAYANG TIMUR ARABICA COFFEE - Nugrahana Fitria Ruhyana; Mardianis Mardianis; Herlina Roseline; Sekar Nur Wulandari (Pusat Penelitian, Badan Keahlian DPR RI, 2022)
To improve the competitiveness and business efficiency of Java Preanger Arabica Coffee (JPAC) from Mount Manglayang Timur, Sumedang Regency, West Java, information is needed regarding the coffee products flow from upstream to downstream, along with the problems faced by each component of the supply chains, the added value of coffee processing, and follow-up plan to develop the JPAC Manglayang Timur business. This study aimed to answer those questions. The research used a mixed-method, a descriptive approach to describe the coffee supply chains and developing plans, and the Hayami method to analyze the coffee value-added. This study was conducted in Sumedang Regency, the production center of JPAC Manglayang Timur. The researcher collected data from interviews, observation, and Focus Group Discussions with resource persons selected by purposive and snowball methods. The results showed 2 (two) JPAC supply chain patterns based on market orientation, namely exports and domestics. Business actors consisted of farmers, farmer groups, large traders/wholesalers, processing industries, cafes or coffee shops, and household consumers. The issues faced by the business actors were the limitations of agro-input and processing equipment, and the lack of marketing integration among business actors. Specialty coffee processed from JPAC Manglayang Timur, specifically the wine processed, has higher value-added than natural, fully-washed, and honey processed coffee. The capacity of coffee farmers needs to be improved o produce specialty coffee that can compete globally through the support of government regulations and synergy between stakeholders from upstream to downstream so that JPAC can become a superior commodity for Sumedang Regency.Keywords: supply chain, value-added, Java Preanger Arabica Coffee, Mountain Manglayang TimurAbstrakDalam upaya meningkatkan daya saing dan efisiensi usaha Kopi Arabika Java Preanger (KAJP) asal Gunung Manglayang Timur Kabupaten Sumedang, Jawa Barat, diperlukan informasi mengenai aliran produk dari hulu hingga hilir, berikut permasalahan yang dihadapi oleh setiap pelaku dalam rantai pasok, nilai tambah dari pengolahan kopi, dan rencana selanjutnya untuk mengembangkan usaha KAJP Manglayang Timur. Penelitian ini bertujuan untuk menjawab berbagai permasalahan tersebut di atas. Metode penelitian menggunakan metode campuran dengan pendekatan kualitatif deskriptif untuk menggambarkan rantai pasok dan rencana pengembangan usaha, serta metode Hayami digunakan untuk analisis nilai tambah. Penelitian dilaksanakan di Kabupaten Sumedang sebagai sentra produksi KAJP Manglayang Timur. Peneliti mengumpulkan data melalui wawancara, observasi, dan Focus Group Discussion dengan narasumber yang dipilih secara purposive dan snowball. Hasil penelitian menunjukkan terdapat dua pola rantai pasok KAJP berdasarkan orientasi pasarnya, yaitu ekspor dan domestik. Pelaku usaha terdiri dari petani, kelompok tani, pedagang besar, industri pengolahan, kafe atau kedai kopi, dan konsumen rumah tangga. Permasalahan yang dihadapi pelaku usaha adalah keterbatasan agro input dan alat pengolahan, serta minimnya integrasi pemasaran antarpelaku usaha dalam rantai pasok. Kopi spesial yang diolah dari KAJP Manglayang Timur, khususnya yang diproses secara fermentasi, dapat memberikan nilai tambah lebih tinggi dibandingkan dengan proses pengolahan secara kering, basah, dan madu. Kapasitas petani kopi perlu terus ditingkatkan agar menghasilkan kopi spesial yang mampu bersaing di pasar global melalui dukungan regulasi pemerintah dan sinergi antar pemangku kepentingan dari hulu hingga hilir sehingga KAJP dapat menjadi komoditas unggulan Kabupaten Sumedang.Kata kunci: rantai pasok, nilai tambah, Kopi Arabika Java Preanger, Gunung Manglayang Timur